Economic benefits to conserve a tourist resource case playa Chifron Puno Peru - Roldán Clará, Blanca; Calatayud Mendoza, Alfredo; Panca-Galindo, Jhesus W. (2021)
The present research work starts from the current problem that the Chifron beach tourist resource faces, which is the contamination by solid waste (garbage) that are left by the visitors who arrive at the beach and this causes a great environmental concern to local people. That is why there is awareness of the impact produced, and it is necessary to give an initiative with this work, which seeks to quantify the willingness to pay, on the part of visitors to conserve this tourist resource.